2016
DOI: 10.1364/ol.41.000348
|View full text |Cite
|
Sign up to set email alerts
|

Negative reflection from metal/graphene plasmonic gratings

Abstract: We propose a scheme of metal/graphene plasmonic gratings for negative reflection. The existence of graphene ribbons, introducing abrupt discontinuity on tangential components of magnetic fields for scattering waves across a graphene interface, substantially alters the dispersion of surface states on plasmonic gratings such that negative reflection that is robust against the incidence angle and can be tuned in a wide frequency range as a function of Fermi energy of graphene. Circularly polarized incidence waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Consequently, various metasurfaces have been proposed for the arbitral control of reflected or transmitted light [ 143 , 144 , 145 ]. These metasurfaces when integrated with graphene could allow the electrical tuning of light direction using principles (ii) and (iii), as discussed in the Introduction [ 146 , 147 , 148 , 149 ]. In this regard, graphene also offers an additional advantage in that it does not affect the optical constant of the overall structure but rather modulates only the resonance because of the extreme thinness of graphene layers.…”
Section: Reconfigurable Reflectorsmentioning
confidence: 99%
“…Consequently, various metasurfaces have been proposed for the arbitral control of reflected or transmitted light [ 143 , 144 , 145 ]. These metasurfaces when integrated with graphene could allow the electrical tuning of light direction using principles (ii) and (iii), as discussed in the Introduction [ 146 , 147 , 148 , 149 ]. In this regard, graphene also offers an additional advantage in that it does not affect the optical constant of the overall structure but rather modulates only the resonance because of the extreme thinness of graphene layers.…”
Section: Reconfigurable Reflectorsmentioning
confidence: 99%
“…MIM-PMAs serve as a platform to enhance graphene absorption and realize high-performance graphene-based photodetectors [ 81 , 111 , 112 , 114 ]. The Fermi level of graphene can be electrically tuned according to the applied voltage; therefore, the absorption wavelength [ 117 ], reflection angle [ 118 ], and phase [ 119 , 120 ] can be electrically tuned by the applied voltage for graphene.…”
Section: Advanced Structures and Applicationsmentioning
confidence: 99%
“…11,12 However, because of the asymmetrical reflection angle distribution of the reflected gradient metasurface, the negative reflection realized by such gradient metasurface that shown in Figure 1(b) is totally different from the wide-angle negative reflection that realized by the phononic crystal 27 and the negative reflection phenomena discussed in other works. 28,29 Recently, Xie, Y. et al 16 reported the apparent negative refraction on a transmissive gradient acoustic metasurface when the incident angle is beyond the critical angle and pointed out that supercell periodicity has play an critical role when analyzing the wave manipulation behaviors of the gradient acoustic metasurface. The apparent negative refracted angle can be calculated by the generalized law of refraction that modified by an additional reciprocal lattice vector term.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%